1999
DOI: 10.1046/j.1469-0705.1999.14040237.x
|View full text |Cite
|
Sign up to set email alerts
|

Central arterial hemodynamics in small‐for‐gestational‐age fetuses before and during maternal hyperoxygenation: a Doppler velocimetric study with particular attention to the aortic isthmus

Abstract: ARED in the aortic isthmus appears to be an early sign of blood flow redistribution in this group of fetuses. Maternal oxygenation results in velocity waveform changes that suggest an increase of cerebral vascular resistance and a redistribution of blood from the brain to the vascular beds supplied by the descending aorta. The aortic isthmus is a suitable site to verify this response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…An increase in middle cerebral artery peak systolic velocity can subsequently be detected (14). Brain-sparing can also be identified by absence or reversal of end-diastolic flow in the aortic isthmus (15). A feature of advanced blood flow redistribution is the ability to visualize coronary blood flow on Doppler sonography, indicating maximal redistribution to the fetal heart ("heart-sparing") (11).…”
Section: Prenatal Circulatory Adaptationsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in middle cerebral artery peak systolic velocity can subsequently be detected (14). Brain-sparing can also be identified by absence or reversal of end-diastolic flow in the aortic isthmus (15). A feature of advanced blood flow redistribution is the ability to visualize coronary blood flow on Doppler sonography, indicating maximal redistribution to the fetal heart ("heart-sparing") (11).…”
Section: Prenatal Circulatory Adaptationsmentioning
confidence: 99%
“…In late-onset IUGR (beyond 30 wk gestational age), the umbilical artery indices usually remain within normal limits (16). Doppler abnormalities are frequently limited to signs of brainsparing such as an abnormal pulsatility index of the middle cerebral artery and absent or reversed end-diastolic flow in the aortic isthmus (15,16).…”
Section: Prenatal Circulatory Adaptationsmentioning
confidence: 99%
“…The observation of fetal AAS with a small, thin, underfilled LV, ultimately manifesting as a completely normal LV after birth, has led us to investigate the possibility of recreating this phenomenon before birth. Maternal hyperoxygenation in the third trimester of pregnancy has been applied in a number of conditions, both from a diagnostic and therapeutic perspective. It can promote fetal pulmonary vasodilation, thereby influencing the quantity of pulmonary venous return to the left side of the heart.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these accepted uses for maternal hyperoxygenation, it has been suggested that maternal oxygen therapy may be associated with increased fetal cerebral vascular resistance, based on sheep 6,7 and human fetal 8,9 data. The cause for increased cerebral resistance with hyperoxygenation may be concurrent hypocapnia, which is known to cause systemic arterial as well as cerebral vascular constriction 10 .…”
Section: Introductionmentioning
confidence: 99%